(3JbfjGJ GdeYdheGJ hGSJNOGeGJgG aj GdefXeGJ GdeYGUQIs - (3HSGe YHO GdQMef(B, (3jhSa GdjhRHcjs ((3YeGf(B:s (3TQcI OGQ GdCcGOjejhf ddfTQ hGdJhRjY(B,s, 2022)
(3eONd JYQjaj HJbfjGJ GdeYdheGJ, eaghe JbfjGJ GdeYdheGJ hGJLGgGJgG GdacQjI, CgejI JbfjGJ GdeYdheGJ Ydh eSJhi GdefXedGJ hGdCaQGO, YdGbI JbfjGJ GdeYdheGJ HNUGFU GdeYdheGJ, OhQ JbfjGJ GdeYdheGJ aj JWhQ CfXeI GdeYdheGJ, eQGMd JWhQ JbfjGJ GdeYdheGJ, GdCLRGA GdeGOjI dJbfjGJ GdeYdheGJ, JYQja GdCLRGA GdeGOjI, JbfjGJ GdEONGd, JbfjGJ GdeYGdLI GdeQcRjI, JbfjGJ GdENQGL, JbfjGJ GdJNRjf, JbfjGJ GdefGaP hGdehUdGJ, CfhGY GdMhGSjH GdeSJNOeI aj efXeGJ GdCYeGd, GdechfGJ GdHQeLjI dJbfjGJ GdeYdheGJ, HQeLjGJ GdfXe, GdHQeLjGJ GdJWHjbjI, JWhQ GdHQeLjGJ hdZGJ GdHQeLI, JbfjGJ GdEJUGdGJ hGdTHcGJ hJWHjbGJgG aj efXeGJ GdCYeGd , eaghe THcGJ GdMGShH, acQI Yed THcGJ GdMGShH, hSGFW (B((3WQGFb(B) (3GdEJUGd GdTHcj, ahGFO GdTHcGJ, CfhGY GdTHcGJ, JbfjGJ GdeYdheGJ hJWHjbGJgG aj GdefXeGJ, GdJbfjGJ GdeSJNOeI aj GdEOGQI GdeGdjI, EOGQI GdEfJGL, EOGQI GdehGQO GdHTQjI hEOGQI GdJShjb hGdJLGQI GdEdcJQhfjI, JbfjGJ GdeYdheGJ hOhQgG aj GdCfTWI GdEOGQjI hMeGjI GdeYdheGJ , GdJCKjQGJ GdSdHjI dJbfjGJ GdeYdheGJ Ydi GdYGedjf hGdHjFI, GdLhGfH GdEOGQjI GdeJYdbI HJbfjGJ GdeYdheGJ, GdCOhGQ GdeYGUQI dJbfjGJ GdeYdheGJ aj efXeGJ GdCYeGd hHjFJgG(B. s
(3eQGLY U(B.247s
Keywords: (3GJNGP GdbQGQGJs; (3JbfjGJ GdeYdheGJs; (3fXe GdeYdheGJs; (3fXe GdeYdheGJ GdEOGQjIs